The Mindful Parenting of Kyai in Pesantren - Akmal Mundiri; Uswatun Hasanah; Hasan Baharun (STAI Hubbulwathan Duri, 2022)
Parenting is an important topic for discussion because it plays a key role in children's education. A child's inherent character reflects how well their education has been carried out, and this includes both teachers and parents. Pesantren caregivers, known as Kyai, are highly regarded for their work in fostering good character in their charges. However, it has also been able to maintain the pesantren's leadership succession while still adhering to the core values and beliefs that are the foundation of the pesantren. The success of the Kyai family can be seen in their children, who have taken on leadership roles in their communities and in Islamic boarding schools. As a result, this research aims to shed light on the prophetic values-based mindful parenting practices of Kyai and his wife. A qualitative case study methodology is employed in this study. A series of methods were used to gather data, including direct observations and interviews. The Miles and Huberman data analysis technique was used to reduce, display, and verify the data collected during the data collection process. The pre-conception and post-conception periods of the mindful parenting process based on prophetic values are examined in this research. Parents who practice prophetic values in the pre-conception period are guided in their choices for a partner, pray for godly children, and provide positive stimulation and nourishment with halal-thoyyib food intake. Parenting is also carried out in the post-conception period through Sharia rituals, such as giving attention and affection, exemplifying and indoctrinating, and asserting one's authority.